Cosmological Distance Scale. Part 16: Hubble Dipole - Levin, S. F. (Measurement techniques, 2023)
The paper considers significant cosmological events that occurred in 2007: the reason for discrepancies in Hubble constant estimates was established; the galactic polar redshift anisotropy within the spectra of extragalactic sources was indicated; a cold spot of cosmic microwave background was detected; the so-called extraordinary evidence of the accelerated expansion of the universe was obtained. This evidence is based on analyzing data on Type Ia supernovae belonging to the Hubble Deep and Ultra Deep Fields. A chain of results is described that led to an alternative hypothesis — acceleration of large-scale galactic flows under the action of the gravitational dipoles of large-scale inhomogeneity of the universe in the form of “giant void–massive supercluster” pairs on opposite sides of the celestial sphere. The author presents the results of testing (for inadequacy) the Friedmann–Robertson–Walker isotropic model of the calibration function of the cosmological redshift distance scale adopted in this extraordinary evidence. It is shown that structural changes and rank inversions of the isotropic model are interpreted as the action of gravitational dipoles due to the existence of a more accurate anisotropic model of the calibration function of the cosmological redshift distance scale. This hypothesis is an alternative to that about the accelerated expansion of the universe. It is shown that the Hubble Deep and Ultra Deep Fields are a gravitational dipole — Hubble dipole.